Avro data - Cutting, Doug.; Safari eBooks; O'Reilly strata making data work conference (2011 : Santa Clara, Calif.) ([United States?] : O'Reilly Media, 2011)
"Apache Avro provides an expressive, efficient standard for representing large data sets. Avro data is programming-language neutral and MapReduce-friendly. Hopefully it can replace gzipped CSV-like formats as a dominant format for data." --Resource description page.
Title from title screen.
Recorded at O'Reilly strata making data work conference: Feb. 1-3, 2011, Santa Clara, Calif.
Electronic reproduction.
Keywords: Data mining; Electronic books